Preparation, characterization, and in vitro diffusion study of nonwoven electrospun nanofiber of curcumin-loaded cellulose acetate phthalate polymer - Ravikumar, Rramaswamy (Saudi Pharm J, 2017)
Novel curcumin (CUR)-loaded cellulose acetate phthalate (CAP) nonwoven electrospun nanofiber (NF) transdermal mat was developed and evaluated for its in vitro CUR diffusion properties. Various CAP solutions from 5 to 20 wt% were tested; 17.5 wt% was found to be a suitable concentration for NF fabrication without defects, such as bubble or ribbon structures. The selected wt% CAP solution was loaded with CUR and electrospun into NFs. The prepared CUR-loaded NFs were characterized using scanning electron microscopy, X-ray diffraction, ultraviolet–visible spectroscopy, thermogravimetric analysis (TGA), and in vitro diffusion studies. The as-prepared fibers demonstrated controlled in vitro transdermal delivery of CUR for up to 24 h.